Shift of S-N curves in some fatigue models due to loading cycle asymmetry - Kohout, Jan; Věchet, Stanislav (Heliyon, 2024)
Fatigue (Wöhler's or S-N) curves are usually represented by upper stress of loading cycle in dependence on the logarithm of numbers of cycles to fracture. Increasing mean stress of loading cycle causes a shift of these curves towards higher values of fatigue strength. A successful quantitative description of the high cycle shift was published by Walker. The aim of the paper consists in deriving and verifying the relations describing the shift of fatigue curves in the whole cycle region from ultimate tensile stress to permanent fatigue limit, for the Palmgren, the Kohout-Věchet and the logistic S-N models, using the high-cycle Walker approach.
Keywords: Fatigue modelling; Kohout-Věchet model; S-N curves; Asymmetry of loading cycle; Logistic S–N model; Palmgren model